THE IMPACT OF ANIMATION ON THE LENGTH OF STAY AND RADIUS OF MOVEMENT OF THE EXCURSION-RECREATIONAL TOURISM - Dimitrić, Dragana; Vujko, Aleksandra; Gajić, Tamara; Petrović, Marko (International Journal of Economic Practice and Policy, 2017)
The basic hypothesis from which we started in the paper is the claim that animation of visitors has a direct impact on the length and radius of excursion-recreational tourism. The main objective of the research is to define the role of animation in the choice of tourist detination and length of staying. In the area of ​​the City of Belgrade, there are more protected natural areas and one of them is the Great War Island located at the confluence of the River Sava in River Danube. This area has three protected zones. Temporary population that was the subject of the interview, as well as the Association of Tourist Guides of Serbia occupate one of these zones. We concluded that one of the biggest advantages of developing tourism of the Great War Island is the possibility of developing certain forms of tourism, and one of these forms, the excursion-recreational tourism has multiple positive effects on the population. The paper concluded that the animation proportionally affects the length of stay of tourists, as well as the radius of their movement.